Deleterious effects of gestational diabetes mellitus on the characteristics of the rectus abdominis muscle associated with pregnancy-specific urinary incontinence - Vesentini, Giovana [UNESP]; Barbosa, Angélica M.P. [UNESP]; Floriano, Juliana F. [UNESP]; Felisbino, Sérgio L. [UNESP]; Costa, Sarah M.B. [UNESP]; Piculo, Fernanda [UNESP]; Marini, Gabriela [UNESP]; Nunes, Sthefanie K. [UNESP]; Reyes, David R.A. [UNESP]; Marcondes, João P.C. [UNESP]; Hallur, Raghavendra L.S. [UNESP]; Rozza, Ariane L. [UNESP]; et al. (Elsevier, 2020)
Aims: To evaluate the effects of gestational diabetes mellitus (GDM) on the structural characteristics of the rectus abdominis muscle (RAM) and its indirect effects on pregnancy-specific urinary incontinence (PSUI). Methods: A total of 92 pregnant women were divided into four groups, according to their clinical conditions: non-GDM continent, non-GDM associated PSUI, GDM continent and GDM associated PSUI. The muscle morphometry (histochemistry and immunohistochemistry) for the fiber types and collagen fiber distribution, the ultrastructural analysis (transmission electron microscopy), the protein expression of fiber types and calcium signaling (Western blotting), and the content of types I and III collagen fiber (ELISA) in RAM collected at delivery were assessed. Results: The GDM groups presented a significantly increased number of slow fibers and slow-twitch oxidative fiber expression; decreased fiber area, number of fast fibers, and area of collagen; an increase in central nuclei; ultrastructural alterations with focal lesion areas such as myeloid structures, sarcomere disorganization, and mitochondrial alteration. The PSUI groups presented a considerable decrease in types I and III collagen contents and the localization of collagen fiber. Conclusions: Our data reveal that GDM causes morphological, biochemical and physiological changes in the RAM, and this might predispose women to PSUI.
Keywords: Collagen; Gestational diabetes mellitus; Pregnancy-specific urinary incontinence; Skeletal muscle; Urinary incontinence